The trouble with culture: A speculative account of the role of gypsy/traveller cultures in 'doorstep fraud'. (August 2019) - Phillips, Coretta
This article makes the case for the empirical study of the causative role of culture and ethnicity in offending and criminality. It advocates considering that racist subordination and structural exclusion may produce adaptive cultural practices which in turn contribute to negative outcomes such as crime. This article tentatively uses a case study of 'doorstep fraud', commonly associated with Gypsy/Traveller 'rogue traders' and 'cowboy builders' to engage with this idea. Drawing on conceptual and theoretical developments in anthropology, sociology and criminology, and using data from offender interviews with 'doorstep fraudsters', I examine the opportunities provided by nomadism and family self-employment for crime commission. The article speculates that Gypsy/Travellers' cultures, structurally framed by economic insecurity, political marginalization and hostile social relations with sedentarist society are nonetheless dynamic rather than fixed, often sharing the aspirations and motivations of other ethno-cultural groups.